Investigating Numeracy Skills: How Students Handle Data Representation Challenges - Puspitasari, Septi; Anwar, Lathiful; Sa'dijah, Cholis (Universitas Suryakancana, 2024)
Adequate numeracy skills are essential, yet many students still face difficulties in solving numeracy problems. Previous studies have indicated that one of the challenges encountered by students relates to the representation of data or information in the problems to be solved. Therefore, the purpose of this study is to explore how students with various levels of numeracy skills address these obstacles in problem solving. The method used is descriptive with a qualitative approach, and data collection techniques include triangulation of test results and interviews. The research subjects are 30 eighth- grade students at one of the public junior high schools in Malang Regency. The results obtained show that students at a proficient level can represent data using mathematical expressions (creating patterns), capable students can represent data with words or written text, whereas students at the basic level still struggle with representing data due to difficulties in connecting available information, though they can read the charts presented. Students requiring special intervention are still unable to represent data from the graphs presented, and they also have difficulties in reading and finding information from graphs. Some students still struggle with writing mathematical arguments and reading information, and are not accustomed to contextual problems. Thus, it is advisable for teachers to familiarize students by providing numeracy problems, both PISA or AKM types